Edible Insects and Other Chitin-Bearing Foods in Ethnic Peru: Accessibility, Nutritional Acceptance, and Food-Security Implications. Issue Volume 38:Issues 3(2018) (September 2018) - Manno, Nicola; Estraver, Walter Zelada; Tafur, Cezar Medina; Torres, Carlos Leon; Schwarzinger, Clemens; List, Manuela; Schoefberger, Wolfgang; Coico, Freddy R. Mejìa; Leon, José Mostacero; Battisti, Andrea; Paoletti, Maurizio G.
This study concerns the ecological and economic features of a particular category of complementary foods in ethnic Peru—comprising of insects, crustaceans, snails, and mushrooms— grouped as chitin-bearing foods (CBFs). Data collection was through participatory methods and semistructured interviews with 242 individuals in eight communities/villages from four ethnic populations. We found that, in Peruvian Amazonian Amerindian communities, CBFs are the most relevant protein source during the rainy season. Shrimp ( Macrobrachium sp.), crab ( Hypolobocera peruviana ), palmweevil ( Rhynchophorus palmarum ), leaf-cutter ants ( Atta cephalotes ), and Lepidoptera larvae are common in the Amazonian diet. In Awajún and Ashaninka communities, most interviewed subjects declared significant consumption of CBFs, while a low percentage ate vertebrates every week during the rainy season and even in the dry season. In contrast, highland Quechua people occasionally consume larvae of Lepidoptera and Coleoptera and Quechua-Lamas populations (in the Amazonian region from historical times) consume the most accessible CBFs on a weekly basis. Traditional technologies and methods of semi-cultivation are evidence of a growing economic interest for CBFs. Relevant species have a high nutritional value in terms of chitin, fatty acids, and proteins, as well a high acceptance by the indigenous population. We conclude that Amazonian Amerindians manage these foods not only as a remedy for food shortage during the rainy season, but also as a stable forest resource and year-round agricultural by-product. We conclude that these traditional food practices should be incorporated within local and national agri-food policies to develop their economic potential and bring their social benefits into rural and peri-urban areas of Peru.